IMPLEMENTASI KEGIATAN KESEIMBANGAN DI SENTRA SPORT AND DANCE UNTUK MELATIH MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TKIT IQRA SERANG-BANTEN - Putri Lailiatul Fijriah; Siti Khosiah; Luluk Asmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of balance activities in the sport and dance center to train the gross motor skills of children aged 4-5 years at TKIT IQRA, Serang, Banten. A descriptive qualitative method was used, involving the sport and dance center teacher, the school principal, and 16 children from two Group A classes as research subjects. Data were collected through observation, interviews, documentation, and field notes, then analyzed through data reduction, data display, and conclusion drawing. The results show that the implementation of balance activities ran well through three stages: planning, implementation, and evaluation. In the planning stage, the teacher prepared a teaching module and selected appropriate balance activities. Implementation followed four scaffolding stages: setting up the play environment, briefing before play, guiding during play, and reviewing after play. Evaluation was carried out through direct observation and a checklist assessment. Supporting factors included adequate facilities, infrastructure, and learning media, while inhibiting factors included weather conditions, differences in children's abilities, health conditions, and limited attention during the activity. Overall, most children were able to perform the balance activities optimally, although a few still required further guidance, indicating that the balance activities at the sport and dance center effectively supported gross motor development in children aged 4-5 years.